2020
DOI: 10.21831/jee.v4i2.35829
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Trainer Kit Instalasi Penerangan Listrik Dengan Pelengkap Sensor Di SMK Negeri 1 Sedayu

Abstract: ABSTRACT:This study aims to: (1) produce an electric lighting installation trainer kit with a complement to sensors on the subject of Electrical Lighting Installation, (2) knowing the feasibility of an electric lighting installation trainer kit with sensor attachments in the Electrical Lighting Installation subject. This research is a Research and Development study using the ADDIE method with the stages of Analysis, Design, Development, Implementation, and Evaluation. This research was conducted at Vocational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The results of this study are in line with research conducted by Sukir et al (2017), which proves that the conveyor trainer kit can effectively improve student learning experiences, especially in the cognitive, psychomotor, and affective aspects of PLC practicum learning in Indonesia. Another study conducted by Wahono and Sukir (2020) found that the electric lighting installation trainer kit developed simplifies the learning process and is useful in improving the learning experience. This study is also in line with the research conducted by Marpanaji et al (2017), which showed that the PID controller trainer kit in the practice of learning control systems is feasible to use to improve problem-solving skills and understanding concepts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study are in line with research conducted by Sukir et al (2017), which proves that the conveyor trainer kit can effectively improve student learning experiences, especially in the cognitive, psychomotor, and affective aspects of PLC practicum learning in Indonesia. Another study conducted by Wahono and Sukir (2020) found that the electric lighting installation trainer kit developed simplifies the learning process and is useful in improving the learning experience. This study is also in line with the research conducted by Marpanaji et al (2017), which showed that the PID controller trainer kit in the practice of learning control systems is feasible to use to improve problem-solving skills and understanding concepts.…”
Section: Resultsmentioning
confidence: 99%
“…The design of trainer kits as alternative learning media has been widely developed, such as conveyor trainer kits for learning programmable logic control (Sukir et al, 2017) and development of electrical lighting installation trainer kits (Wahono & Sukir, 2020). The design of the trainer kit by the researcher is the basic electrical and electronics trainer kit based on fault finding.…”
Section: Introductionmentioning
confidence: 99%